2016
DOI: 10.1016/j.neuroimage.2015.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Brain basis of communicative actions in language

Abstract: Although language is a key tool for communication in social interaction, most studies in the neuroscience of language have focused on language structures such as words and sentences. Here, the neural correlates of speech acts, that is, the actions performed by using language, were investigated with functional magnetic resonance imaging (fMRI). Participants were shown videos, in which the same critical utterances were used in different communicative contexts, to Name objects, or to Request them from communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
72
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 72 publications
(133 reference statements)
11
72
1
3
Order By: Relevance
“…This may help to translate the broad knowledge about syntactical aspects of language to the domain of action, where our knowledge about syntax is still strongly limited. With the current overview and outlook, we suggest that future investigations are essential to comprehensively describe the language-action interrelation and for understanding how action is related to language in ontogeny (Egorova et al, 2016;Leshinskaya & Caramazza, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may help to translate the broad knowledge about syntactical aspects of language to the domain of action, where our knowledge about syntax is still strongly limited. With the current overview and outlook, we suggest that future investigations are essential to comprehensively describe the language-action interrelation and for understanding how action is related to language in ontogeny (Egorova et al, 2016;Leshinskaya & Caramazza, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, traditional accounts of cognition assume conceptual representations as amodal, thus independent from representations in the perceptual and motor systems of the brain (Repetto et al, 2012). On the other hand, recent accounts argue that representations of different formats such as language and action are not independent from each other but (highly) intertwined (Egorova, Shtyrov, & Pulvermüller, 2016). Accordingly, actions and bodily experiences are considered necessary for cognitive processing and their interplay is crucial, especially regarding the development of higher order capabilities (Engel, Maye, Kurthen, & König, 2013).…”
mentioning
confidence: 99%
“…Using behavioral measures of motor activity (e.g., grip force and posture changes), listening to action‐related verbs in sentences induces motor activity (da Silva, Labrecque, Caromano, Higgins, & Frak, ; Shiller et al, ), and however, this may be modulated by semantic context (Aravena et al, ). Studies using fMRI, TMS, MEG, and the EEG mu rhythm have found activation of the motor system when adults process (hear or read) verbs or phrases about actions (Di Cesare, Errante, Marchi, & Cuccio, ; Egorova, Shtyrov, & Pulvermüller, ; Hauk, Johnsurde, & Pulvermüller, ; Moreno et al, ; Moreno, de Vega, & León, ) or while decoding degraded speech sounds (d'Ausilio, Bufalari, Salmas, & Fadiga, ). Indeed, there is evidence that the motor system is functionally linked to representing action‐related language (Vukovic, Feurra, Shpektor, Myachykov, & Shtyrov, ), and some studies have also found left‐hemisphere specificity for the action‐language link (e.g., Pulvermüller, Hauk, Nikulin, & Ilmoniemi, ).…”
Section: Mirroring and Communicationmentioning
confidence: 99%
“…In addition to the timing of action recognition, brain areas and circuits activated in this process have also been explored in some fMRI studies, mainly using overhearer paradigms (Bašnáková, van Berkum, Weber, & Hagoort, 2015;Bašnáková, Weber, Petersson, Van Berkum, & Hagoort, 2014;Egorova, Shtyrov, & Pulvermüller, 2016;van Ackeren, Casasanto, Bekkering, Hagoort, & Rueschemeyer, 2012). These studies contrasted direct and indirect actions and found that interpreting indirect actions activated theory of mind areas in the brain (related to thinking about other's intentions) more than direct actions.…”
Section: Recognizing Actionsmentioning
confidence: 99%